Factores que determinan las capacidades cognitivas de investigación en estudiantes universitarios durante la pandemia del covid-19. - Fuster-Guillén, Doris; Ocaña-Fernández, Yolvi; Norabuena Figueroa, Roger Pedro; Morillo-Flores, John (Archivos Venezolanos de Farmacología y Terapéutica, 2022)
Among the primary objectives of higher education is to train researchers capable of providing solutions to specific problems. In this task, there are a series of events that need to be elucidated. The purpose of the research work was to explain the factors that determine cognitive research abilities. The study was developed with a mixed approach and a concurrent triangulation design that allowed corroborating qualitative and quantitative data simultaneously. The sample consisted of 303 university students from a public institution to whom two questionnaires were applied linked to factors that determine cognitive abilities in research, which were subjected to construct validity through the exploratory analysis of the factor with the theta coefficient (θ = 0.790) and omega (ω = 0.778); while, in the case of investigative capacities, it was theta (θ = 0.650) and omega (ω = 0.692). Both cases showed an acceptable level of reliability. The semi-structured interview was used for experts and students. The factor that determined the research capacity was the orientation of the teacher of the research methodology in 29% and the initial research training factor in 16%; while the factor that did not determine the investigative capacity was research ethics. 32.3% of the students have developed research skills of reflection, specifically, in the search, choice and argumentation of the background of the research work and the problematic situation.